Identification of the components for investigation of the psychological strength of nursing applicants: A qualitative study. Issue 6 (14th June 2021) - Bagheriyeh, Farzaneh; Ghahramanian, Akram; Valizadeh, Leila; Zamanzadeh, Vahid; Dickens, Geoffrey
Abstract: Aim: There is a lack of clarity about the components which would signify appropriate psychological strengths among nursing student candidates. This study was conducted to identify such components from the viewpoint of the clinical nurses and nursing instructors. Design: A qualitative study. Methods: This study comprised qualitative research using a conventional content analysis approach. Participants were 25 nurses and nursing instructors. Data were collected in audio‐recorded and transcribed semi‐structured interviews and were analysed using MAXQDA10 software. Results: Analysis revealed four main categories including "anger management, " "Stress/distress management, " "self‐belief" and "aptitude for hard work." Conclusions: This study identified core components for future investigations into the psychological strengths of nursing applicants. This study provides specific testable hypotheses for future research endeavours. It is recommended that the researchers investigate the appropriateness of the components identified in this study to assess the psychological strength of the applicants in the longitudinal studies.